Enhancing tribological performance: A comprehensive review of graphene-based additives in lubricating greases - Ethan Stefan-Henningsen; Nathan Roberts; Amirkianoosh Kiani (Results in Engineering, 2025)
The integration of carbon-based additives, such as graphene, graphene ox- ide (GO), and reduced graphene oxide (rGO), into lubricating greases has attracted significant interest in the field of tribology. These materials exhibit unique properties such as exceptional mechanical strength, low interlayer shear resistance, and high thermal conductivity, which act to enhance the performance of lubricating greases. This review paper explores grease formation, types, and performance, focusing on the potential advantages and limitations of graphene derivatives as lubricant additives. Graphene has been shown to reduce friction and wear, improve load-carrying capacity, and enhance thermal stability through various research projects. Despite the promising results, challenges such as effective dispersion, scalability of synthesis, and grease structure compatibility remain. This paper provides a comprehensive overview of current research, highlighting the benefits, limitations, and future directions for graphene-based additives in lubricating greases.